¿PUCULLOS? IN WARPA, URUBAMBA AND MANTARO RIVER BASIN, BETWEEN AYACUCHO Y HUANCAVELICA, PERU - Valdez Cárdenas, Julio Ernesto (2014)
Innovative information of the existence of architectonic structures forged with stones and clay those funerary cameras that are strategically constructed in large rocks form shows up in this article and to the shade of big stones block or rocks that enable your dryness. These types of cameras come themselves locating at the surroundings of the basin of the river Warpa and in your confluence with the river Mantaro, at territories of Ayacucho’s and Huancavelica’s department, in the Peru.